2020
DOI: 10.1039/d0fo01234c
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a homopolysaccharide with hypoglycemic activity from the roots of Pueraria lobata

Abstract: A water-soluble neutral homopolysaccharide (PLP-1) was obtained from the roots of Pueraria lobata by DEAE cellulose and Sephadex G-200 gel chromatography purification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…FOXO1 is the main regulator of redox balance in osteoblasts. When high glucose induces an increase in oxidative stress, it can stimulate FOXO1 secretion [ 34 36 ]. Via integrated signals originating from the bone, FOXO1 can change the function and mass of pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOXO1 is the main regulator of redox balance in osteoblasts. When high glucose induces an increase in oxidative stress, it can stimulate FOXO1 secretion [ 34 36 ]. Via integrated signals originating from the bone, FOXO1 can change the function and mass of pancreatic β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mosialou et al also found that the upregulation of LCN2 is a protective mechanism against glucose intolerance caused by obesity by reducing food intake and promoting adaptive β-cell proliferation. Osteoblast-derived LCN2 suppress appetite and reduce fat mass, while improving glucose metabolism [ 34 ]. Both FOXO1 and LCN2 can be secreted by osteoblasts, and can participate in regulation of glucose metabolism by affecting the mechanism of insulin resistance during the pathogenesis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, membranes were incubated with an ECL kit for visualization (Yeason, Shanghai, China). The density of each band was quantified using Image Lab software (Qian et al, 2020).…”
Section: Western Blot Analysesmentioning
confidence: 99%
“…It has been shown that the polysaccharide PLP-1 extracted from P. lobata has a hypoglycemic effect in vitro. 24 In our laboratory's early stages of research, the crude polysaccharide PL70-1 was extracted and separated from P. lobata by hot water extraction and ethanol precipitation method, and the polysaccharide PL70-1-1 was then puried by column chromatography, and proved that they have a hypoglycemic effect. 25 The isolation and identication of polysaccharides from P. lobata and the explanation of its biological activity need to be further studied.…”
Section: Introductionmentioning
confidence: 99%